2010
DOI: 10.3109/02656736.2010.483635
|View full text |Cite
|
Sign up to set email alerts
|

Fever-range whole body thermotherapy combined with oxaliplatin: A curative regimen in a pre-clinical breast cancer model

Abstract: Purpose Studies were conducted to test whether fever-range whole body hyperthermia, rationally combined with oxaliplatin chemotherapy, would boost its efficacy without substantial toxicity. Materials and Methods The effect of heat on oxaliplatin cytotoxicity, cellular uptake, and platinum-DNA adduct formation was studied in vitro using the MTLn3 tumor cell line. In vivo, oxaliplatin was given with thermal therapy to rats bearing highly treatment-resistant MTLn3 mammary adenocarcinomas at various doses and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…The viability of cells treated with F-108@TPP-AuNP,b ut not subjected to the laser irradiation,w as reducedb y2 1%,p rimarily due to an enhanced mechanism of delivery.T he viability of cells incubated with F-108@TPP-AuNP and then subjected to laser irradiationd ecreased by ac onsiderable 58 %, demonstrating the pronounced and long-term effect of hyperthermia in conjunction with the delivery of TPP.S tudies have demonstrated that cancerc ells are sensitivet oi ncreasei nt emperature, with cells at 39 8Cw eakened and more sensitivet oc hemotherapy. [37] Treatmento fc ells with ac ytotoxic compound can result in a variety of cell fates including (i)necrosis, (ii)cytostasis and (iii)apoptosis. To determine which of these phenotypesw ere induced by TPP delivery, we treated HeLa cells for 4h with TPP-Au I Cl or F-108@TPP-AuNP and compared them to cells treated with no additive as controls.…”
Section: Resultsmentioning
confidence: 99%
“…The viability of cells treated with F-108@TPP-AuNP,b ut not subjected to the laser irradiation,w as reducedb y2 1%,p rimarily due to an enhanced mechanism of delivery.T he viability of cells incubated with F-108@TPP-AuNP and then subjected to laser irradiationd ecreased by ac onsiderable 58 %, demonstrating the pronounced and long-term effect of hyperthermia in conjunction with the delivery of TPP.S tudies have demonstrated that cancerc ells are sensitivet oi ncreasei nt emperature, with cells at 39 8Cw eakened and more sensitivet oc hemotherapy. [37] Treatmento fc ells with ac ytotoxic compound can result in a variety of cell fates including (i)necrosis, (ii)cytostasis and (iii)apoptosis. To determine which of these phenotypesw ere induced by TPP delivery, we treated HeLa cells for 4h with TPP-Au I Cl or F-108@TPP-AuNP and compared them to cells treated with no additive as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this study demonstrated that DC vaccination in combination with hyperthermia resulted in an increased infiltration of activated CD8 + cells into the tumor site accompanied by decreased infiltration of immune suppressive T reg cells, possibly creating an environment for improved tumor control (44). Recently long-term anti-tumor immunity was achieved in murine models; treatment with oxaliplatin chemotherapy followed twenty-four hours later by six hour whole body hyperthermia was able to cure all primary and metastatic tumors in 50% of MTLn3 tumor-bearing rats (13). …”
Section: Discussionmentioning
confidence: 99%
“…Based on a growing literature, it is apparent that the effect of hyperthermia on anti-tumor immunity is quite complex impacting various arms of the innate and adaptive immune response (11, 12). Excitingly, very recent studies in a clinically relevant animal model have demonstrated that adding hyperthermia to chemotherapy results in a curative therapy that is immunologically mediated (13). It has been widely reported that tumor infiltrating lymphocytes are essential for the inhibition of tumor growth and improved prognosis in various cancer types (14–19).…”
Section: Introductionmentioning
confidence: 99%
“…The cellular uptake of oxaliplatin and platinum-DNA adduct was measured as described previously [47] but with slight modifications. MCF-7 cells were divided into three groups with 5× 10 6 MCF-7 tumor cells per group and treated as follows: control group, 5% glucose solution at 37°C for 6 h; oxaliplatin group, 20 μg oxaliplatin/mL at 37°C for 6 h; OML group, 20 μg oxaliplatin/mL at 37°C for 6 h. Then, 1.6 mL of resuspension liquid of cell pellet with PBS in each group was divided into three parts and tested for a given parameter, as follows: 0.3 mL, cellular uptake; 0.2 mL, protein concentration; and 1.1 mL, DNA concentration and DNA adduct.…”
Section: Methodsmentioning
confidence: 99%